2016
DOI: 10.1523/jneurosci.0580-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Lynx1 Limits Dendritic Spine Turnover in the Adult Visual Cortex

Abstract: Dendritic spine turnover becomes limited in the adult cerebral cortex. Identification of specific aspects of spine dynamics that can be unmasked in adulthood and its regulatory molecular mechanisms could provide novel therapeutic targets for inducing plasticity at both the functional and structural levels for robust recovery from brain disorders and injuries in adults. Lynx1, an endogenous inhibitor of nicotinic acetylcholine receptors, was previously shown to increase its expression in adulthood and thus to l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 44 publications
1
31
0
Order By: Relevance
“…Sajo et al also demonstrated that after MD, while spine gain rate of layer 5 neurons becomes comparable between adult Lynx1KO mice and adult WT mice due to MD-induced increase in spine gain in WT mice (Hofer et al, 2009), spine loss rate remains significantly higher in Lynx1KO mice compared to WT matched controls in both layer 5 and 2/3 neurons (Sajo et al, 2016). These results suggested that, while spine gain rate correlates well with the residual plasticity in the normal adult V1, higher spine loss seems to be a good correlate of elevated juvenile-like functional plasticity in adult Lynx1KO mice.…”
Section: Regulation Of Critical Period Closure By Lynx1 An Endogementioning
confidence: 97%
See 3 more Smart Citations
“…Sajo et al also demonstrated that after MD, while spine gain rate of layer 5 neurons becomes comparable between adult Lynx1KO mice and adult WT mice due to MD-induced increase in spine gain in WT mice (Hofer et al, 2009), spine loss rate remains significantly higher in Lynx1KO mice compared to WT matched controls in both layer 5 and 2/3 neurons (Sajo et al, 2016). These results suggested that, while spine gain rate correlates well with the residual plasticity in the normal adult V1, higher spine loss seems to be a good correlate of elevated juvenile-like functional plasticity in adult Lynx1KO mice.…”
Section: Regulation Of Critical Period Closure By Lynx1 An Endogementioning
confidence: 97%
“…If nicotinic cholinergic signaling could regulate critical period plasticity, then how would then plasticity become severely restricted in adulthood even in the remaining presence of robust basal forebrain cholinergic innervation? Here we introduce Lynx1, an allosteric cholinergic modulator that increases into adulthood after critical period, and review its contribution to regulate functional and structural plasticity in the V1 (Bukhari et al, 2015; Morishita et al, 2010; Sajo et al, 2016). The discovery of the role of nicotinic cholinergic modulator Lynx1 as a plasticity regulator has given light to a new perspective – the brain is intrinsically plastic even in adulthood, but is actively masked by molecular plasticity “brakes” (Bavelier et al, 2010).…”
Section: Regulation Of Critical Period Closure By Lynx1 An Endogementioning
confidence: 99%
See 2 more Smart Citations
“…The inability for CGE-derived neurons to induce plasticity also suggests that the mechanisms required to home the transplanted cells into the host cortical network are not enough to elicit functional reorganization. Endogenous critical period closure has been associated with the expression of molecular brakes that stabilize mature cortical networks (Bavelier et al, 2010; Morishita et al, 2010; Sajo et al, 2016). Transplanted PV and SST cells may alter the expression of such brakes and thus allow host cells to rewire upon sensory deprivation.…”
Section: Transplantation and Cortical Plasticitymentioning
confidence: 99%